The Influence of Word of Mouth, Packaging, Price Perception, and Product Quality on the Purchasing Decision of Bolu Kelapa Gumregah - Primasari, Naresthi; Astuti, Widhy Tri; Arif, Nina Fapari (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study investigates the influence of word of mouth, packaging, price perception, and product quality on consumer purchasing decisions for Bolu Kelapa Gumregah, a locally produced cake by KEP Desa PRIMA Gumregah in Gunungkidul, Yogyakarta. As a flagship product rooted in local cultural practices such as ulih-ulih, understanding consumer decision-making is critical for sustaining its market growth. Employing an explanatory research design and survey methodology, data were collected from 50 purposively selected consumers and analyzed using multiple linear regression. The results reveal that while the four variables collectively have a significant effect (F = 43.470; p < 0.001) and explain 65.6% of the variance in purchasing decisions, only price perception demonstrates a positive and statistically significant individual effect (β = 0.709; p < 0.001). Word of mouth, packaging, and product quality show no significant individual impact. These findings underscore the dominant role of price perception in consumer behavior and highlight the need for strategic marketing efforts focused on perceived value. The study contributes to the literature on community-based micro-enterprises and offers practical recommendations for enhancing local product competitiveness through pricing, packaging, and quality alignment.